PENGGUNAAN PASIR LAHAR DINGIN DI KALI PUTIH SEBAGAI AGREGAT HALUS BETON - Fatkhurrohim Fatkhurrohim; Ahmad Mashadi; Muhammad Amin; Dwi Sat Agus Yuwana (Universitas Tidar, 2018)
ABSTRACTAfter the eruption of Mount Merapi, which occurred on October 26th 2010 produced an abundance of cold lava sand. The researcher attempted to conduct test of cold lava sand as fine aggregate concrete. This study aims to compare the compressive strength of concrete by using a cold lava sand taken from the Kali Putih, Salam, Magelang and sand are not affected by cold lava taken from Kali Blondo located in the Blondo, Magelang. The method of this study include: testing of materials, manufacturing of test specimens and test concrete performance after 7, 14, 21 days and 28 days. From the test result of concrete compressive strength we can know strength combaine ineach mixtureby weight volume ratio 1pc: 2 ps; 3kr with 0,6 water cement ratio. Based on the results of testing the quality of the sand material taken from the Kali Putih, Salam, Magelang to the mud content, unit weight, specific gravity, water absorption,and sieve analysis PUBI 1982 qualifies mixed concrete.The result of comparative testing of the quality of the sand material taken from kali blondo to sieve analysis are not eligible PUBI 1982. The results showed that the compressive strength of concrete on average, the highest shown in the concrete that uses cod lava sand derived from the down stream of Kali Putih, the average compressive strength of 279,51 kg/cm2, with the weight of the specimen by an average of 11, 5 kg.